The notion of reverse solicitation within the realm of financial services - Zieds, Niklāvs (Riga Graduate School of Law, 2019)
The objective of this thesis is to analyse the scope and current restrictions of the reverse solicitation regime vis-à-vis European financial services law. Given the reliance on ambiguous terminology, ill-defined concepts and inconsistencies throughout MiFID II, the analysis throughout the work concludes that the concept of reverse solicitation in its current form cannot be reliably utilised by third-country financial service providers due to numerous inadvertent non-compliance risks. The study concludes that the current reverse solicitation regime needs to be heavily revised to allow for a sufficient degree of legal certainty.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law